A huge serpentine embolic intracardiac thrombus: A rare manifestation of Behcet's disease - Mohamed El Minaoui, MD; Amine EL Houari, MD (Radiology Case Reports, 2022)
Behcet's disease is a systemic vasculitis that can manifest as an intracardiac thrombus, which is rare but a serious complication. We report a case of a young male with a history of diabetes mellitus and erythema nodosum, who was admitted for pulmonary embolism associated with a huge serpentine right ventricle thrombus leading to the diagnosis of Behcet's disease. The patient was managed medically with a favorable evolution. The development of intracardiac thrombus is a life-threatening manifestation of the disease, and its discovery, especially in young subjects must suggest the diagnosis of Behcet's disease even if there is no predisposing ethnic or geographical factor.